A post-Soviet Republic in Transition: A Novel Amplification Programme to Address the Crisis of Continuing Medical Education and Challenges Facing Regional Physicians in the Republic of Armenia. Issue 1 (1st January 2020) - Chekijian, Sharon Anoush; Simonyan, Hambardzum; Yaghjyan, Gevorg
ABSTRACT: Background: After the fall of the Soviet Union in 1991, the existing process of Continuing Medical Education (CME) was decimated. The Fund for Armenian Relief (FAR) was able to leverage competitive educational fellowship programmes in existence, and harness new knowledge gained by returning fellows thus amplifying the impact on education and patient care in the regions of the republic of Armenia. Aims: This manuscript describes a replicable novel amplification programme using a "train the trainer" model for CME in the republic of Armenia. We sought to identify challenges specific to physicians from the regions, and to examine the strengths of the CME programme that can serve as a model for programme development and improvement in countries facing similar challenges. Methods: The manuscript details a descriptive and mixed method study that includes in-depth interviews and focus group discussions from 2015–2016. Conceptual content analysis was used to identify major themes from the transcripts. Results: Challenges facing regional physicians in post-Soviet counties in transition, exemplified by Armenia, are profound. Exploration of themes related to perceived barriers to care in the regions included, physicians' personal financial constraints, lack of up-to-date knowledge and equipment, lack of confidence, fear of criticism and of making incorrect diagnoses. Conclusions: The FAR/CME programme presents an innovative way to amplify the knowledge of Armenian physicians upon their return from educational programme participation abroad in order to address challenges facing regional physicians.